Racial disparities in supportive medication use among older patients with brain metastases: a population-based analysis. Issue 9 (9th March 2020) - Lamba, Nayan; Mehanna, Elie; Kearney, Rachel B; Catalano, Paul J; Haas-Kogan, Daphne A; Alexander, Brian M; Cagney, Daniel N; Lee, Kathleen A; Aizer, Ayal A
Abstract: Background: Brain metastases (BM) cause symptoms that supportive medications can alleviate. We assessed whether racial disparities exist in supportive medication utilization after BM diagnosis. Methods: Medicare-enrolled patients linked with the Surveillance, Epidemiology, and End Results program (SEER) who had diagnoses of BM between 2007 and 2016 were identified. Fourteen supportive medication classes were studied: non-opioid analgesics, opioids, anti-emetics, anti-epileptics, headache-targeting medications, steroids, cognitive aids, antidepressants, anxiolytics, antidelirium/antipsychotic agents, muscle relaxants, psychostimulants, sleep aids, and appetite stimulants. Drug administration ≤30 days following BM diagnosis was compared by race using multivariable logistic regression. Results: Among 17, 957 patients, headache aids, antidepressants, and anxiolytics were prescribed less frequently to African Americans (odds ratio [95% CI] = 0.81 [0.73–0.90], P < 0.001; OR = 0.68 [0.57–0.80], P < 0.001; and OR = 0.68 [0.56–0.82], P < 0.001, respectively), Hispanics (OR = 0.83 [0.73–0.94], P = 0.004 OR = 0.78 [0.64–0.97], P = 0.02; and OR = 0.63 [0.49–0.81], P < 0.001, respectively), and Asians (OR = 0.81 [0.72–0.92], P = 0.001, OR = 0.67 [0.53–0.85], P = 0.001, and OR = 0.62 [0.48–0.80], P < 0.001, respectively) compared with non-Hispanic Whites. African Americans also received fewer anti-emetics (OR = 0.75 [0.68–0.83], P < 0.001), steroids (OR = 0.84 [0.76–0.93], P < 0.001), psychostimulants (OR = 0.14 [0.03–0.59], P = 0.007), sleep aids (OR = 0.71 [0.61–0.83], P < 0.001), and appetite stimulants (OR = 0.85 [0.77–0.94], P = 0.002) than Whites. Hispanic patients less frequently received antidelirium/antipsychotic drugs (OR = 0.57 [0.38–0.86], P = 0.008), sleep aids (OR = 0.78 [0.64–0.94, P = 0.01), and appetite stimulants (OR = 0.87 [0.76–0.99], P = 0.04). Asian patients received fewer opioids (OR = 0.86 [0.75–0.99], P = 0.04), anti-emetics (OR = 0.83 [0.73–0.94], P = 0.004), anti-epileptics (OR = 0.83 [0.71–0.97], P = 0.02), steroids (OR = 0.81 [0.72–0.92], P = 0.001), muscle relaxants (OR = 0.60 [0.41–0.89], P = 0.01), and appetite stimulants (OR = 0.87 [0.76–0.99], P = 0.03). No medication class was prescribed significantly less frequently to Whites. Conclusions: Disparities in supportive medication prescription for non-White/Hispanic groups with BM exist; improved provider communication and engagement with at-risk patients is needed. Key Points: 1. Patients with BM commonly experience neurologic symptoms. 2. Supportive medications improve quality of life among patients with BM. 3. Non-White patients with BM receive fewer supportive medications than White patients.